Description of two new species and new records of the genus Epilachna Chevrolat (Coleoptera: Coccinellidae) in Peru - Bustamante-Navarrete, Abdhiel Arnaldo (2018)
Epilachna lucianae n. sp. and Epilachna matei n. sp. are described using specimens collected in the Peruvian regions of Huanuco and Cusco; new records are also provided for some species of the genus Epilachna Chevrolat for Peru.